Effect of minimum quantity lubrication on surface roughness in tool-based micromilling - Ali, Mohammad Yeakub; Jailani, Wan Norsyazila; Abd Rahman, Mohamed; Hassan, Muhammad Hasibul; Banu, Asfana (International Islamic University Malaysia-IIUM, 2017)
Cutting fluid plays an important role in machining processes to achieve dimensional accuracy in reducing tool wear and improving tool lifespan. The conventional flood cooling method in machining processes is not cost effective and consumption of huge amounts of cutting fluid is neither healthy nor environmentally friendly. In micromachining, flood cooling is not recommended to avoid possible damage to the microstructures. Therefore, one of the alternatives to overcome the environmental issues is to use a minimum quantity of lubrication (MQL) in the machining process. MQL is ecofriendly and has an economical advantage in manufacturing costs. However, there is an observed lack of study on MQL in improving machined surface roughness in micromilling. A study of the effects of MQL on surface roughness should be carried out because surface roughness is one of the important issues in micromachined parts such as microfluidic channels. This paper investigates and compares surface roughness with the presence of MQL and dry cutting in the micromilling of aluminium alloy 1100 using a DT-110 milling machine. The relationship between the depth of cut, feed rate, and spindle speed on surface roughness is also analyzed. The three machining parameters identified as significant for surface roughness with dry cutting are: depth of cut, feed rate, and spindle speed. For surface roughness with MQL, it is found that spindle speed did not greatly influence surface roughness. The presence of MQL provides a better surface roughness by decreasing the friction between tool and work piece.